Formulação de extratos vegetais e fúngico para controle alternativo de doenças no feijoeiro - Viecelli, Clair Aparecida (2012)
The bean (Phaseolus vulgaris) has a significant economic and social importance, but the production is affected by fungal diseases such as angular leaf spot (Pseudocercospora griseola) and common bacterial blight (Xanthomonas axonopodis pv. phaseoli), which depend primarily of chemical control for the management, compromising, however, environmental quality and health of the farmer and consumer. In order to develop an alternative product that respects the environment, dry extract of rosemary (Rosmarinus officinalis), turmeric (Curcuma longa) and Pycnoporus sanguineus were submited to accelerated stability tests, antimicrobial activity, effects on vegetative growth of bean and efficiency in reducing the severity of that disease. Thus were used concentrations of 50, 100, 150 and 200 mg L-1, water and chemical fungicides (azoxystrobin 40 mg L-1) for angular leaf spot and antibiotic (22.5 mg L-1 + oxytetracycline 225 mg L-1 streptomycin) for common bacterial blight. The best result was field-tested on area under the disease progress curve (AUDPC) and on aspects of productivity. To the extract of rosemary, the results report that the validity is 24 months. To turmeric extracts and P. sanguineus the validity depending on the pathosystem, and to angular leaf spot, the validity of the extract of turmeric is 24 months, and when it seeks to control bacterial blight shelf life is 18 months. Likewise, extract of P. sanguineus to control angular leaf spot the validity of 24 months and for the bacterial blight 12 months. In vitro, only rosemary extract showed no antimicrobial activity on P. griseola, the other treatments tended to inhibit the germination of P. griseola and the multiplication of X. axonopodis pv. phaseoli. All treatments tended to increase fresh and dry mass of shoots and roots of beans. The severity of both diseases in the greenhouse was not reduced for the extract of P. sanguineus, but was reduced for concentrations of 150 mg L-1 for rosemary extract and 50 mg L-1 for turmeric. Those latter concentrations were tested in the field with 1, 2 and 3 shots at intervals of 14 days after planting. In the field, the dry extract of rosemary reduced the AACPD and increased the productivity (kg ha-1) with one application 14 days after planting. To angular leaf spot, and with three applications for common bacterial blight. To the extract of turmeric, it is suggested three applications for controlling both diseases. These treatments were similar to chemical controls. Thus study conducted with rosemary and turmeric provides an efficient product for the control of angular leaf spot and bacterial blight of bean. These products, along with P. sanguineus, are being tested in different cultures to disease control, and may extend the recommendation for other plants, being a viable alternative and environmentally friendly for agricultural production, respecting the environment, the producer and consumer